2008
DOI: 10.2151/jmsj.86.429
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Trend in Rainfall over Indochina during the Late Summer Monsoon: Impact of Tropical Cyclones

Abstract: We examined the decreasing trend in rainfall during the late summer monsoon season (September) in Thailand from 1951 to 2000 and associated changes in tropical cyclone (TC) activity. Thailand receives significant rainfall from May to October and experiences two rainy peaks in late May to early June and in September. A previous study reported a decreasing trend in September rainfall in Thailand and, based on a regional climate model, suggested that the trend was associated with local deforestation. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 16 publications
4
47
1
Order By: Relevance
“…Seasonal variations in probability for a WNP TC to move into the SCS are likely related to changes in major TC tracks among different months. TC tracks are generally considered to be highly controlled by steering flows, which are normally represented by 500-hPa circulations (e.g., Wu and Wang 2004;Camargo et al 2007;Takahashi and Yasunari 2008). The seasonal features of steering flows are delineated by 1950 -2010 means of 500-hPa winds and height.…”
Section: Seasonal Modulations Of Large-scale Circulationsmentioning
confidence: 99%
“…Seasonal variations in probability for a WNP TC to move into the SCS are likely related to changes in major TC tracks among different months. TC tracks are generally considered to be highly controlled by steering flows, which are normally represented by 500-hPa circulations (e.g., Wu and Wang 2004;Camargo et al 2007;Takahashi and Yasunari 2008). The seasonal features of steering flows are delineated by 1950 -2010 means of 500-hPa winds and height.…”
Section: Seasonal Modulations Of Large-scale Circulationsmentioning
confidence: 99%
“…However, weaker TCs, including tropical depressions and residual lows, can also bring rainfall. Takahashi and Yasunari (2008) showed that weaker TCs also contribute to the total rainfall. To estimate TC activity including that of weaker TCs, the perturbation kinetic energy (PKE) of the low level winds was defined using high frequency components of u and v, i.e.,…”
Section: Methodsmentioning
confidence: 99%
“…For example, Singh et al (2000) showed that the frequency of TCs over the north Indian Ocean has increased in May and November and weakened in September over the last 100 years, which was likely to affect long-term changes in rainfall. Takahashi and Yasunari (2008) and Takahashi et al (2009) analyzed observational data and proposed that the long-term decrease in September rainfall over Indochina in the second half of the twentieth century, which was found by Kanae et al (2001), could be explained by the weakening of TC activity over the South China Sea and Philippine Sea regions in September. In addition, Takahashi et al (2009) found that the long-term decrease in rainfall over the Indochina Peninsula was most significant along the eastern coast of Vietnam, where rainfall is strongly affected by TC activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most Southeast Asian regions experience a simple summertime rainfall maximum during the Asian summer monsoon period, the maximum rainfall period in central Vietnam is from November to December (Matsumoto, 1997;Yokoi et al, 2007). Although some studies have been conducted to understand the mechanisms and characteristics of rainfall over Vietnam (e.g., Yokoi and Matsumoto, 2008;Takahashi and Yasunari, 2008;Chen et al, 2012;Nguyen-Thi et al, 2012;Takahashi, 2012), large knowledge gaps remain. One of the reasons is that the rain-gauge network in Vietnam is still not dense enough to meet the demands of practitioners and researchers.…”
Section: Introductionmentioning
confidence: 99%